Comparison of Recover Heart Rate Status among 4th Year Male Sport Science Summer Program Students, Wollega University, Ethiopia - Jabesa, Edosa (Journal of Sports Research, 2018)
This study aimed to experiment, measure and evaluate the level of recovery heart rate among male sport science students of the summer program and to compare their mean with the standard status of the recover heart rate rating scale. From a total population of 80, the sample consisted of 40 male sports science students. The samples were selected by using a random sampling technique. The subjects were divided into two equal sections on a random basis (section A, and section B) consisting of 20 subjects in each group. Harvard step test was used to measure the recovery heart rate of the students' wich is an index of cardiovascular fitness. To compare the mean differences among the students independent t test was applied with the help of SPSS (version, 20) Software. The level of significance was set at 0.05. The findings of the current study show that the mean value of recovery heart rate for section A was calculated 104.2 with S.D. 3.4 and section B was recorded 106.8 with S.D. 2.24 respectively. The t-value on recovery heart rate is 2.924 which are greater than the required table value (2.021) with 38 df. So there is a statically significant difference in the recovery heart rate variable between section A and section B sport science students. There were statistically significant mean differences in recovery heart rate among the section A and section B male students, also the recovery heart rate level of the subjects was below the standard level of recovery heart rate rating scale.